Use of ‘Pharmaceutical services’ Medical Subject Headings (MeSH) in articles assessing pharmacists' interventions - Tonin, Fernanda (2022)
Background: Medical Subject Headings (MeSH) thesaurus contribute towards efficient searching of biomedical information. However, insufficient coverage of specific fields and inaccuracies in the indexing of articles can lead to bias during literature retrieval. Objectives: This meta-research study aimed to assess the use of ‘Pharmaceutical Services’ MeSH terms in studies evaluating the effect of pharmacists' interventions. Methods: An updated systematic search (Jan-2022) to gather meta-analyses comparing pharmacists' interventions vs. other forms of care was performed. All MeSH terms allocated to the MEDLINE record of each primary study included in the selected meta-analyses were systematically extracted. Terms from the ‘Pharmaceutical Services’ branch, including its descendants, as well as other 26 pharmacy-specific MeSH terms, were identified. The assignment of these terms as a ‘Major MeSH’ was also evaluated. Descriptive statistics and social network analyses to evaluate the co-occurrence of the MeSH terms in the articles were conducted. Sensitivity analyses including only meta-analyses with declared objectives mentioning the words ‘pharmacist’ or ‘pharmacy’ were performed (SPSS v.24.0). Results: Overall, 138 meta-analyses including 2012 primary articles were evaluated. A median of 15 [IQR 12–18] MeSH terms were assigned per article with a slight positive time-trend (Spearman rho = 0.193; p < 0.001). Only 36.6% (n = 736/2012) and 58.1% (n = 338/1099) of studies were indexed with one MeSH term from the ‘Pharmaceutical Services’ branch in the overall and sensitivity analyses, respectively. In <20% of cases, these terms were a ‘Major MeSH’. The pharmacy-specific term ‘Pharmacists’ was the most frequently used, yet in only 27.8% and 47.7% of articles in the original and sensitivity analyses, respectively. Social networks showed a weak association between pharmacy-specific and ‘Pharmaceutical services’ branch MeSH terms. Conclusions: The availability of a ‘Pharmaceutical services’ branch hierarchic tree and further pharmacy-specific MeSH terms incorporated into the MeSH thesaurus in the past years is not related to the accurate indexing of articles.